The conservation easement clustering patterns in U.S. urbanizing counties - Dyckman, Caitlin S.; Self, Stella Coker Watson; Lauria, Mickey; White, David L.; Fouch, Nakisha; Ogletree, S. Scott; Overby, Anna T. (Frontiers in Environmental Science, 2025)
Conservation easement (CE) use in the U.S. and globally has expanded over the past 40 years in fringe areas adjacent to urbanization, and this article examines their spatial manifestation in twelve physically and socially heterogeneous, high growth metropolitan U.S. counties within six states. Augmenting previous CE studies relying on single spatial statistical tests, we employed multiple spatial statistics for a more complete picture of CE spatial clustering over time. Our results show nuanced associational—but not causal—spatial relationships between CEs. Ripley’s K and Average Nearest Neighbor results display distinct clustering patterns across most counties over time despite county disparity and CE difference. Global Moran’s I results show that CE size impacts the clustering. Notably, the CEs with a first designated biological purpose did not cluster based on size. Counties with governmental oversight in CE placement lacked a consistent clustering typology, suggesting that other factors have greater influence on CE spatial expression. The results illustrate the importance of using multiple spatial statistical tests to accurately reveal relationships between phenomena across space, as CE clustering affects systematic conservation planning and precision in the hazard model of land development, promotes environmental management responses to climate change biome shifts, and potentially limits development.